Sistem Pemasaran Kayu Rakyat di Kabupaten Bulukumba Sulawesi Selatan - Muh Erwin Syah; Makkarennu Makkarennu; Supratman Supratman (Fakultas Kehutanan, Universitas Hasanuddin, 2018)
This study aims to identify marketing channels and analyze the marketing system. The results of this study are expected to be a study material for the improvement of community forest management in Bulukumba regency, South Sulawesi province, in an effort to improve the welfare of the community, especially forest farmers. The research was conducted in two villages belonging to the Association of People's Wood Management: Karassing Village, Herlang Subdistrict, and Sapobonto Village, Bulukumpa Subdistrict, Bulukumba Regency. Data collection was conducted by semi-structured interviews on marketing actors with snowball method (chain), field survey related to marketing institution, then analyzed by using SCP (structural, conduct, performance) method. From the results of the research, there are three channels of marketing identification: 1) Farmer - Collector - Sawmill Industry - Retail Trader; 2) Farmers - Sawmill Industry - Retail Traders; and 3) APKAR - Wood Processing Industry. The wood marketing system found in APKAR farmers has not been efficient because the overall market structure tends to Oligopsoni, and market behavior that tends to be controlled by the sawmill industry.Keywords: Efisiensi; hutan rakyat; pemasaran; saluran pemasaran; kayu gergajian